FACTOR ANALYSIS OF THE INFLUENCE OF THE EDUCATIONAL ENVIRONMENT ON THE FORMATION OF A FUTURE SPECIALIST PROFESSIONAL READINESS (Education in the 21st Century, 2023)
The purpose of this study was to determine the degree of factors influence of the educational environment of the higher educational institution on the process of formation of professional (hard skills) and social (soft skills) competencies of future specialists. The relevance of the article lies in determining the educational environment potential of a higher educational institution, which consists in the possibility of transforming external pedagogical influences into the internal structure of the personality, its intellectual, moral, spiritual, and physical development. The scientific novelty of the article lies in the combined nature of scientific and pedagogical research, since the work contains theoretical scientific propositions that relate to the essence of the key propositions of the study (educational environment, professional, social competence, specialist, etc.), as well as qualitative summaries of the results of empirical data factor analysis, which are obtained as a result of the quantitative characterization of the factors influence of the internal psychological environment and the external educational space.It has been proven that the educational environment of a higher educational institution contributes to filling the axiosphere of educational activity subjects with ethical-aesthetic, professional-cultural, corporate values, stimulates group interests, enhances formal and interpersonal interaction, helps the assimilation of social experience and the acquisition of qualities necessary for a person to live and in order to stay in the profession, provides the opportunity to acquire general (key) and professional competencies in the humanitarian, social, natural, engineering and technical fields. The accumulation of empirical data was carried out in the process of observing a group of students (n = 925): surveys, questionnaires, testing, and interviews. It is advisable to take into account the results of the study in the process of constructing and implementing a model for graduates of higher educational institutions.